Work‐family conflict and synergy among Hispanics. (2014) - ,; ,
Abstract : Purpose – Hispanics represent a growing segment of the US population and workforce, yet there is a lack of empirical research on Hispanics in relation to work‐family conflict and synergy. Drawing on work‐family and job demands‐resources theories, the authors model predictors (autonomy, schedule flexibility, social support, work hours) and outcomes (health and satisfaction) of work‐family variables among Hispanics and non‐Hispanic whites. The paper aims to discuss these issues.Design/methodology/approach – This quantitative study examined responses from respondents ( n =2, 988) of the 2008 National Study of the Changing Workforce using descriptive statistics, t ‐tests, ANOVAs, and structural equation models (SEM). The paper focusses primarily on Hispanics and also examined gender differences for Hispanics and non‐Hispanic whites.Findings – Hispanic women reported the highest work‐family conflict (work interfering with family (WIF) and family interfering with work (FIW)) and synergy (work‐family synergy (WFS)) levels. Job resources are related to WIF for Hispanic women but not Hispanic men. Autonomy was the best predictor of WFS for all groups. Coping mediated the depression‐life satisfaction relationship. WIF and WFS were each significantly related to job satisfaction. Job satisfaction and life satisfaction were significantly related for all groups except Hispanic women. Job satisfaction‐turnover paths were significant.Research limitations/implications – Although based on a high‐quality national probability sample, all information was gathered from one extensive interview. There is also a need to examine subgroups of Hispanics beyond the scope of this data set.Practical implications – Results suggest similarities as well as differences in work‐family variables for Hispanics and non‐Hispanic whites. Corporate work‐family policies and initiatives may need to be altered in light of ethnicity and gender issues as the workforce becomes more diverse.Originality/value – This study examined work‐family conflict and synergy among Hispanics. The predominance of research on non‐Hispanic whites needed to be extended to different racial/ethnic groups who may experience WIF, FIW, and WFS differently. Acknowledgements : Portions of this paper were presented at the inaugural conference of the Work Family Researchers Network, New York, NY, June 2012. Thanks to SKOPE and the Department of Education, University of Oxford, for office space and technology used to complete portions of this manuscript.